Biomechanical evaluation of syndesmotic fixation techniques via finite element analysis: Screw vs. suture button. (September 2021) - Alastuey-López, Diego; Seral, Belén; Pérez, Mª Ángeles
Highligths: Syndesmotic injured fixation using a 3D finite element model. Important biomechanical differences between screws and suture buttons. Suture button behavior closer to the intact ankle joint Preoperative planning tool for surgery support Abstract: Background and Objective: Tibiofibular syndesmotic injuries may cause degenerative changes, reduction in ankle function and compromising ankle stability. Different fixation techniques try to restore its functionality. Screw-fixation is the gold-standard. Recently, suture-button fixation has aroused the attention because it allows for physiologic micromotion while maintaining an accurate reduction. The aim of this study is to compare the biomechanical behaviour of both fixation techniques using the finite element method. Methods: A three-dimensional finite element model of the tibiofibular joint was reconstructed simulating the intact ankle and the injured syndesmosis. Then, different methods of syndesmosis fixation were analysed: screws (number of cortices, number of screws and distance between screws) and suture buttons (single, double parallel and double divergent with a sensitivity analysis on the pretension forces) configuration. Ligaments and cartilages were included and simulated as spring elements. Physiological loads during stance phase were simulated. Results: Syndesmosis widening and von Mises stresses were computed. Syndesmosis widening in the injured configuration compromised joint stability (2.06 mm), whereas using a single quadricortical screw (0.18 mm) stiffened the joint. Syndesmosis widening using suture-buttons were closer to syndesmosis widening of the intact ankle configuration (0.97 mm). Von Mises stresses were higher for the titanium screws than for the suture buttons. Conclusions: A detailed biomechanical comparison among different syndesmotic fixation was performed. Suture buttons have advantages with regard to syndesmosis widening in comparison to screw fixation. This fact supports the good long-term clinical results obtained with suture buttons fixation. The proposed methodology could be an efficient tool for preoperative planning.